GridPACKTM: A framework for developing power grid simulations on high-performance computing platforms. (May 2016) - Palmer, Bruce; Perkins, William; Chen, Yousu; Jin, Shuangshuang; Callahan, David; Glass, Kevin; Diao, Ruisheng; Rice, Mark; Elbert, Stephen; Vallem, Mallikarjuna; Huang, Zhenyu
This paper describes the GridPACK TM framework, which is designed to help power grid engineers develop software capable of running on high-performance computers. The framework makes extensive use of software templates to provide high-level functionality while still providing flexibility to easily implement a broad range of models and algorithms. GridPACK TM contains modules for setting up distributed power grid networks, supporting application-specific bus and branch models, creating distributed matrices and vectors and using parallel linear and non-linear solvers. It also provides mappers to create matrices and vectors based on properties of the network and functionality to support Input/Output (IO) and to manage errors. The goal of GridPACK TM is to substantially reduce the complexity of writing software for parallel computers while still providing efficient and scalable software solutions. The use of GridPACK TM is illustrated for a simple powerflow example and performance results for the powerflow and dynamic simulations are discussed.